1997
DOI: 10.1097/00004872-199715120-00069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on carotid and radial artery distensibility

Abstract: Acute cigarette smoking reduces distensibility not only in medium-sized but also in large elastic arteries, therefore causing a systemic artery stiffening. The mechanisms of these effects remain to be determined. However, it is likely that adrenergic mechanisms are responsible for the arterial distensibility alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 31 publications
1
77
0
4
Order By: Relevance
“…The role of these two cardiovascular risk factors on arterial stiffness is controversial; most studies have shown the absence of major effect of these two factors on arterial stiffness. 16,25,[26][27][28] Therefore, whereas dyslipidaemia and tobacco have a major role in the atheromatosis process, their contribution to the development of arterial stiffness is not established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of these two cardiovascular risk factors on arterial stiffness is controversial; most studies have shown the absence of major effect of these two factors on arterial stiffness. 16,25,[26][27][28] Therefore, whereas dyslipidaemia and tobacco have a major role in the atheromatosis process, their contribution to the development of arterial stiffness is not established.…”
Section: Discussionmentioning
confidence: 99%
“…13,25 The influence of tobacco smoking and cholesterol level in PWV and arterial stiffness is still controversial. [26][27][28] The determinants of arterial stiffness were mainly assessed in studies which included young and middle-aged populations. 14,18,19 The determinants of PWV in the elderly have been assessed in a limited number of studies.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34] Swampillai et al 35 reported a significant smoking-induced increase in stiffness index (SI) 15 min after smoking (Po0.05), but did not observe changes in wave speed in the carotid artery.…”
Section: Acute Smokingmentioning
confidence: 99%
“…Alteration of the dynamic vessel wall properties has also been considered as an important mechanism since some investigators have demonstrated acute changes of such functional variables as arterial stiffness immediately after smoking. [7][8][9][10][11][12] However, the chronic effects of smoking are uncertain. 7)8)13) Wollersheim et al 13) reported increased arterial stiffness of the popliteal artery and a tendency toward stiffening of the femoral and common carotid arteries in healthy habitual smokers.…”
Section: )2)mentioning
confidence: 99%
“…In addition to several other responsible mechanisms, alteration of the dynamic arterial wall properties is considered to play an important role for smoking related vascular damage. [7][8][9][10][11][12][13] Increased arterial stiffness has been recognized as important marker for the increased risk of cardiovascular disease and it is an independent predictor of all-cause and cardiovascular death. 14)15) The acute increase in arterial stiffness, blood pressure and heart rate after smoking may enhance the load on the arterial walls and the left ventricular wall, and this can induce alteration in the distribution of the circumferential stress and tensile stress.…”
Section: )22)mentioning
confidence: 99%